Readiness for non-communicable disease service delivery in Ethiopia: an empirical analysis - Azeb Gebresilassie Tesema; Rohina Joshi; Seye Abimbola; Alemnesh H. Mirkuzie; Daria Berlina; Tea Collins; David Peiris (BMC, 2024)
Abstract Background Ethiopia's health system is overwhelmed by the growing burden of non-communicable diseases (NCDs). In this study, we assessed the availability of and readiness for NCD services and the interaction of NCD services with other essential and non-NCD services. Methods The analysis focused on four main NCD services: diabetes mellitus, cardiovascular diseases, chronic respiratory diseases, and cancer screening. We used data from the 2018 Ethiopian Service Availability and Readiness Assessment (SARA) survey. As defined by the World Health Organization, readiness, both general and service-specific, was measured based on the mean percentage availability of the tracer indicators, such as trained staff and guidelines, equipment, diagnostic capacity, and essential medicines and commodities needed for delivering essential health services and NCD-specific services, respectively. The survey comprised 632 nationally representative healthcare facilities, and we applied mixed-effects linear and ordered logit models to identify factors affecting NCD service availability and readiness. Results Only 8% of facilities provided all four NCD services. Availability varied for specific services, with cervical cancer screening being the least available service in the country: less than 10% of facilities, primarily higher-level hospitals, provided cervical cancer screening. General service readiness was a strong predictor of NCD service availability. Differences in NCD service availability and readiness between regions and facility types were significant. Increased readiness for specific NCD services was significantly associated with increased readiness for communicable disease services and interacted with the readiness for other NCD services. Conclusion NCD service availability has considerable regional variation and is positively associated with general and communicable disease services readiness. Readiness for specific NCD services interacted with one another. The findings suggest an integrated approach to service delivery, focussing holistically on all disease services, is needed. There also needs to be increased attention to reducing resource allocation variation between facility types and locations.